Implementation of interpreter object oriented design pattern on basis of XML language - Tsukur, V.; Drobnych, O.; Plakosh, Yu. (Інститут проблем математичних машин і систем НАН України, 2007)
This article describes programmatic issues and solutions while implementing XML-based Interpreter Object Oriented Design Pattern.Aims and usage of such Interpreter are presented. Language elements and their implementation for Java 2 are described. Refs.: 5titles.